A Systematic Literature Review at Integrating Ethnomedicine into Project-Based Learning: Enhancing Higher-Order Thinking Skills in Pharmaceutical Education - Faizul Bayani; Joni Rokhmat; Aliefman Hakim; AA Sukarso (Jurnal Penelitian Pendidikan IPA, 2024)
Project-Based Learning (PjBL) is an innovative pedagogical approach that fosters Higher-Order Thinking Skills (HOTS), including critical thinking, creativity, and problem-solving, essential for 21st-century education which are crucial for success in 21st-century education. This systematic literature review explores the integration of ethnomedicine into PjBL frameworks, focusing on pharmaceutical education. Using PRISMA guidelines and bibliometric analysis with VOSviewer, 6,499 documents from Scopus were screened, resulting in seven key studies. Findings reveal that combining ethnomedicine with PjBL enhances culturally relevant learning, bridging traditional medicinal practices with modern education. This interdisciplinary approach improves cognitive skills, contextual learning, and cultural preservation, but challenges such as institutional readiness and knowledge variability persist variability in knowledge remain. The study underscores the need for further research and policy support to optimize this promising educational model.